“PICS”: a novel patient-specific landmark for thalamic surgical interventions in the posterior limb of the internal capsule signal - Patriat, Rémi; Chandrasekaran, Jayashree; Sretavan, Karianne; Braun, Henry; Brenny, Samuel; Seddighi, Yasamin; Aman, Joshua E.; Hill, Meghan; Vitek, Jerrold L.; Harel, Noam; Almeida, Leonardo (Frontiers in Human Neuroscience, 2025)
IntroductionDifficulties in direct visualization of thalamic subnuclei are likely a contributor to inconsistent surgical outcomes among patients with medication refractory tremors. We present a new MRI landmark, represented by a bright signal in the posterior limb of the internal capsule signal (PICS), that can serve as a consistent marker for indirect location of the Vim nucleus of the thalamus. We evaluated the visibility of PICS across multiple MRI sequences at 7Tesla (T) and 3T, and its anatomical characteristics were identified using tractography.MethodsOne healthy control and 15 essential tremor (ET) patients were scanned. To characterize the PICS fibers, two posterior limb of internal capsule (pLIC) tractography schemes were conducted with cortical ROIs as seeds and the pLIC as a waypoint: (i) gross motor cortical ROIs, (ii) M1 and S1 homunculus. Finally, intra- and post-operative clinical data were merged for one ET DBS patient to show correspondence between the parcellation results and clinical observations.ResultsPICS was consistently identified across multiple MRI sequences. Tractography analyses identified PICS to correlate with the distribution of motor fibers from the internal capsule. For the M1 homunculus, two somatotopic clusters were observed: one including mostly trunk, lower and upper limbs; and another, more anteriorly, with head/face clustering with tongue/larynx. For the S1 homunculus, the trunk region was overall the most posterior region followed by the upper limb/face anteriorly and Area2. Intra-operative stimulation at two different depths resulted in pLIC-specific side effect in the tongue/face. At those depths, measurements showed closer proximity of the DBS electrode to M1 clusters of head/face and tongue/larynx, validating the imaging findings.ConclusionPICS appears to be a reliable radiological marker comprising cortico-spinal tracts, in isolation from corticobulbar tracts fibers. It is consistently located lateral to the Vim, making it a potential landmark to infer Vim location and help refine targeting for thalamic procedures. The parcellations of the pLIC using M1 homunculus could potentially inform lead or ablation location based on side effect profiles (e.g., head/face/tongue vs. trunk/limbs). Therefore, proximity or distance to PICS may potentially guide lead placement to avoid procedure-related capsular side effects while optimizing benefits.